Estimation of Load Torque and Rotor Speed in Single-Phase Induction Motor Using EKF - Ali Monadi; Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris (Institute of Advanced Engineering and Science, 2015)
This paper presents a novel method for estimation of load torque and rotor speed in single-phase Induction Motor (IM) with two asymmetrical windings by using Extended Kalman Filter (EKF). Normally, for estimation of load torque and rotor speed in IM, six state variables namely stator currents, rotor fluxes, rotor speed and load torque, are considered. This paper shows by considering five state variables, estimation of these parameters is possible. Simulation results show the good performance of the presented method. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7592